THE CORRELATION BETWEEN STUDENTS’ TIKTOK USE AND VOCABULARY MASTERY - Harum Natasha; Salsabila (Journal of English and Arabic Language Teaching, 2026)
This study aims to examine the correlation between sixth-semester students’ habit of exploring TikTok as a social media platform and their vocabulary mastery in the English Education Department at UIN Sultan Syarif Kasim Riau. The study involved 30 students selected using simple random sampling from a population of 119 students. Data was collected through a questionnaire measuring TikTok usage habits and a multiple-choice vocabulary test. Results from the Pearson product-moment correlation test indicate a significant relationship between students’ social media habits and vocabulary acquisition, with a significance value of 0.000 < 0.05. These findings suggest that regular engagement with TikTok, particularly English-language content, may contribute positively to vocabulary development. The study highlights the potential of integrating digital media platforms such as TikTok into language-learning strategies, while also noting the need to balance informal learning with academic language acquisition. Future research could explore specific content types that most effectively support vocabulary growth.